2000
DOI: 10.1042/ba19990086
|View full text |Cite
|
Sign up to set email alerts
|

Examination of bioaffinity immobilization by precipitation of mannan and mannan-containing enzymes with legume lectins

Abstract: The interaction of four lectins from crops of the legume family with Saccharomyces cerevisiae alpha-mannan, and also with two glycoenzymes containing mainly alpha-mannan moieties, has been studied. The interaction was characterized by a quantitative precipitation assay. The results of precipitation differ with respect to both quality (the point of maximum precipitation) and of the quantity (the amount of aggregated lectin and saccharide). The lectin concanavalin A [Con A, from jack bean (Canavalia ensiformis)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…12 -14 Ease of immobilization, lack of chemical modification and usually accompanying enhancement in stability are some of the advantages offered by the bioaffinity-based procedures, which also offer the additional benefit of orienting the enzyme favorably on the support. 15, 16 These supports have been used for the high yield and stable immobilization of glycoenzymes/enzymes. Bioaffinity-based procedures can be employed for the immobilization of enzymes directly from the crude homogenate or partially purified enzyme preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 -14 Ease of immobilization, lack of chemical modification and usually accompanying enhancement in stability are some of the advantages offered by the bioaffinity-based procedures, which also offer the additional benefit of orienting the enzyme favorably on the support. 15, 16 These supports have been used for the high yield and stable immobilization of glycoenzymes/enzymes. Bioaffinity-based procedures can be employed for the immobilization of enzymes directly from the crude homogenate or partially purified enzyme preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier reports described that the immobilization of glycoenzymes on Con A support resulted in the stabilization of enzymes against various forms of denaturation. 12,16 Protease resistance is an additional attribute of the bioaffinity-based immobilization of BGP. It indicated that Con A-Sephadex-bound BGP preparation has great potential in the treatment of organic pollutants present in industrial effluents.…”
mentioning
confidence: 99%
“…This process can immobilize enzyme directly from crude homogenate overcoming the high cost of purification which employs commercially available enzyme/expensive supports [12]. Besides conferring ease to immobilize proteins, other advantages of such protocols include lack of chemical modification, proper orientation of enzyme on the support, high yield and enhanced stability of glycoenzymes/enzymes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lectins are proteins which recognize and interact with exposed carbohydrate moieties of glycoproteins and glycoenzymes. These proteins are useful in characterizing glycoproteins and certain glycoenzymes have been immobilized on concanavalin A affinity matrices or as Con A-glycoenzyme complexes [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Bioaffinity-based procedures, due to their reversibility, lack of chemical modification and their usually accompanying stability enhancement are emerging as powerful strategies for the immobilization of several enzymes (Saleemuddin & Husain 1991;Saleemuddin 1999;Mislovicova et al 2000;McMahon & Mulcahy 2002). The strong affinity of polyclonal/monoclonal antibodies for specific enzymes and those of lectins for glycoenzymes bearing appropriate oligosaccharides have been generally employed for this purpose (Shami et al 1991;Husain & Saleemuddin 1986, 1989.…”
Section: Introductionmentioning
confidence: 99%